The main psychological and spiritual features of the trickster in the literature (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article devotes to look tricster problem in the world Literature. The chief attention allots quality and feature tricster psychologist .
Keywords: tricster; psychologist